Taisui TS-2007S, a Large Microbial Mat Discovered in Soil in China - Su, Tongfu; Liu, Haohao; Zhang, Chaohui; Shang, Di; Wang, Chaojiang; Qiu, Liyou (Frontiers in Microbiology, 2020)
In this study, Taisui TS-2007S, a previously the unidentified biological object, discovered in soil in China, was identified. TS-2007S was shown to contain abundant carbohydrates but a scarcity of protein, fat, and minerals. The exopolymers of TS-2007S showed FT-IR spectra that were similar to those of xanthan gum but that were dissimilar to those of polyvinyl alcohol (PVA). The NMR spectra of TS-2007S exopolymers in D2O were similar to those of PVA but differed from those of xanthan gum. Unlike PVA, TS-2007S exopolymers and xanthan gum were not soluble in dimethyl sulfoxide (DMSO). Furthermore, the exopolymers contained many monosaccharide components, including fucose, rhamnose, mannose, and glucuronic acid in a molar ratio of 87.90:7.49:4.45:0.15. The exopolymers also included traces of glucuronic acid, galactose, and xylose. Taken together, these results suggest that the exopolymers are microbial extracellular polymeric substances (EPS). The microbial community structure in TS-2007S showed that the predominant bacterial, archaeal and fungal phyla were Proteobacteria, Euryarchaeota and Ascomycota at high relative abundances of 90.77%, 97.15%, and 87.43%, respectively, different from those observed in water and soil environments. Based on these results, we strongly propose that TS-2007S should be defined as a microbial mat formed in soil.